Emotional Stress, Heart Rate Variability, Grounding, and Improved Autonomic Tone: Clinical Applications. - Chevalier, Gaétan; Sinatra, Stephen T (Integrative Medicine: A Clinician's Journal)
Over the last few years, the utilization of integrative biophysics for medical application has been increasing in popularity. Grounding or earthing is the oldest and most basic form of natural bioelectric potential that supports physiological and electrophysiological changes in the body. Since previous investigations have shown that grounding profoundly affects skin conductance within seconds, we hypothesized that grounding may also improve heart rate variability (HRV). In this study of 27 final participants, grounded subjects had improvements in HRV that go beyond basic relaxation (P<.01). Since improved HRV has such a positive impact on cardiovascular status, it is suggested that simple grounding techniques be utilized as a basic integrative strategy in supporting the cardiovascular system, especially under situations of heightened autonomic tone (ie, when the sympathetic nervous system is more activated than the parasympathetic nervous system).